A smooth vetch (Vicia villosa var.) strain endogenous to the broad-spectrum antagonist Bacillus siamensis JSZ06 alleviates banana wilt disease - Ruan, Yan-Nan; Nong, Caihong; Jintrawet, Attachai; Fan, Huacai; Fu, Libo; Zheng, Si-Jun; Li, Shu; Wang, Zhi-Yuan (Frontiers in Plant Science, 2024)
Fusarium wilt, caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4), poses a significant threat to banana production globally, thereby necessitating effective biocontrol methods to manage this devastating disease. This study investigates the potential of Bacillus siamensis strain JSZ06, isolated from smooth vetch, as a biocontrol agent against Foc TR4. To this end, we conducted a series of in vitro and in vivo experiments to evaluate the antifungal activity of strain JSZ06 and its crude extracts. Additionally, genomic analyses were performed to identify antibiotic synthesis genes, while metabolomic profiling was conducted to characterize bioactive compounds. The results demonstrated that strain JSZ06 exhibited strong inhibitory activity against Foc TR4, significantly reducing mycelial growth and spore germination. Moreover, scanning and transmission electron microscopy revealed substantial ultrastructural damage to Foc TR4 mycelia treated with JSZ06 extracts. Genomic analysis identified several antibiotic synthesis genes, and metabolomic profiling revealed numerous antifungal metabolites. Furthermore, in pot trials, the application of JSZ06 fermentation broth significantly enhanced banana plant growth and reduced disease severity, achieving biocontrol efficiencies of 76.71% and 79.25% for leaves and pseudostems, respectively. In conclusion, Bacillus siamensis JSZ06 is a promising biocontrol agent against Fusarium wilt in bananas, with its dual action of direct antifungal activity and plant growth promotion underscoring its potential for integrated disease management strategies.